Genome-Wide Analysis and Expression Tendency of Banana (Musa acuminata L.) Calcineurin B-Like (MaCBL) Genes under Potassium Stress - Ying Xiong; Ruimei Li; Xuejun Lin; Yangjiao Zhou; Fenlian Tang; Yuan Yao; Jiao Liu; Lixia Wang; Xiaomin Yin; Yongxia Liu; Jianchun Guo; Yan Zhao; et al. (Horticulturae, 2021)
Calcineurin B-like (CBL) proteins are reported to play significant roles in plant development and ion-transport regulation. Potassium shortages are a serious problem in banana cultivation. However, to date, the members of the banana CBL gene family, and their function in regulating potassium stress, remain unclear. In this study, 11 CBL genes were identified from the banana genome and grouped into four groups (Group I–IV) based on their phylogenetic relationships. The genomic features of these MaCBL genes were analyzed, focusing on their gene structures, standpat motifs, chromosomal distributions, and evolutionary history. Expression pattern analysis revealed that the MaCBLs were function-specific. Further qRT-PCR analysis indicated that the presence of MaCBL2 was indeed a response to potassium deficiency stress. The MaCBL2 gene was cloned, and sequence alignment indicated that it contained four elongation factor hand (EF-hand) domains, the conserved N-terminal myristoylation domain “MGCXXS/K(T)” and the “FPSF” motif. Subcellular location analysis showed that MaCBL2 was located in the plasma membrane, nucleus and cytoplasm. The overexpression of MaCBL2 could restore the growth of the yeast mutant R5421 on a K+-deficient medium. The overexpression of MaCBL2 could promote the root length of transgenic seedlings on K+-deficient medium. These findings indicate that MaCBL2 was, in our study, the key gene of the CBL family in responding to potassium deficiency in bananas. Our discoveries have established a considerable basis for the further study and application of MaCBL genes.